A parallel-group study of near-infrared spectroscopy-neurofeedback in children with attention deficit hyperactivity disorder - Wu, Wen-Jun; Cui, Long-Biao; Cai, Min; Peng, Zheng-Wu; Zhang, Wen-Chao; Lv, Shuai; Xu, Jia-Yu; Hu, Yang; Li, Guanya; von Deneen, Karen M.; Zhu, Chao-Zhe; Wang, Hua-Ning; et al. (Psychiatry research, 2022)
•This parallel-group study assessed the efficacy of Near-infrared spectroscopy (NIRS) based neurofeedback (NF) compared to atomoxetine(AT) on patients with ADHD.•Up to now, our trial is one of the few trials performed to evaluate its efficacy relative to medication. In this trial, NIRS-NF was an effective intervention for ADHD patients.•During the observation of 8 weeks, Patients in NIRS group showed significant efficacy in inattention, compared to AT group at week 3 and week 6.•At the same time, NIRS group had faster reaction time (RT) during Go/No-Go task and less errors during N-back than AT group.•The findings of this study reveal that NIRS-NF improves the behavioral performance more compared to AT, highlighting its potential role in treating patients with ADHD. The present study aimed to assess the efficacy of Near-infrared spectroscopy (NIRS) real-time neurofeedback (NF) vs. atomoxetine (AT) in children with attention deficit hyperactivity disorder (ADHD). A parallel-group study was conducted to enroll children with ADHD between 8 and 12 years of age. Participants were assigned into the NIRS group and AT group as their wish. Subjects in the NIRS group received 12 sessions of NF training within 6 weeks, and subjects in the AT group were given oral medication. Changes in Swanson, Nolan, and Pelham-V rating scales (SNAP-IV), and performance of Go/No-Go and N-back working memory tasks at week 3, 6 and 8 were evaluated. Forty-nine patients completed the study, including 18 ADHD in the NIRS group and 31 in the AT group. Total scores of SNAP-IV significantly decreased from baseline to week 3, week 6, and week 8 in both groups. Patients in the NIRS group showed significant lower scores on the inattention subscale of SNAP-IV at week 3 and week 6, compared to the AT group. NIRS group had a shorter reaction time during the Go/No-Go task at week 6 and fewer errors during 2-back than the AT group at week 3. The findings revealed that NIRS real-time NF is more efficacious relative to AT in improving behavioral performance, highlighting its potential role and advantages in treating patients with ADHD.